Implementation of the Community-Based Total Sanitation (STBM) Partnership Program, Pillar 4, in the Working Area of Public Health Center I, North Denpasar - Saraswati, Anak Agung Sagung Ratu Putri; Cempaka, Pande Putu Ayu Rissa; Arisanthi, Gusti Agung Ayu Nanda (Babali Nursing Research, 2026)
Introduction: In 2025, Denpasar City recorded the highest waste volume in Bali, averaging 1.005 tons per day. Overall, Bali is in a waste emergency with a total daily output of 3.436 tons, of which 64,86% is organic waste. Implementing the fourth pillar of STBM is one solution to addressing domestic waste by involving active community participation. The study aimed to determine the implementation of the partnership for STBM pillar 4 in the working area of Puskesmas I North Denpasar. Methods: This study employed a descriptive quantitative approach with the STBM verification data collection method. The population comprised all households in North Denpasar. Sampling was conducted in 5 sub-districts, encompassing 16 banjars. The samples were taken from 40 households. Results: 76.8% of households have not managed their waste. Meanwhile, only 23.3% of households have managed their waste. The presentation results for the four criteria for good and correct waste management are 67.25% of households have maintained a clean home environment by not allowing waste to be scattered. A total of 54.25% of families have closed, sturdy, and easy-to-clean trash cans, yet about half still lack adequate waste disposal facilities. 55.75% of families have implemented safe waste management practices. Only 35.5% of families have sorted their waste. Conclusion: The implementation of STBM pillar 4 in the Puskesmas I North Denpasar working area is still not optimal. The success of this pillar is not only about the availability of trash bins; it also requires a more comprehensive approach that fosters active community participation through partnership programs in waste sorting and management